Respostas
respondido por:
1
x^2 -(x^4-10x^2+25)=3
x^2--x^4+10x^2-25=3
-x^4+11x^2-28=0
x^4-11x^2+28=0
(x^2)^2-11x^2+28= 0
K^2 -11k + 28=0
∆= 121-112
∆= 9
K= 11+ou -√9/2
K' = 11+3/2=14/2
K'= 7
K"= 11-3/2= 8/2=4
x^2= +ou - √7
x'= √7 ou x"= -√7
x= +/-√4
x'= √4=2 ou x"= -√4=2
x^2--x^4+10x^2-25=3
-x^4+11x^2-28=0
x^4-11x^2+28=0
(x^2)^2-11x^2+28= 0
K^2 -11k + 28=0
∆= 121-112
∆= 9
K= 11+ou -√9/2
K' = 11+3/2=14/2
K'= 7
K"= 11-3/2= 8/2=4
x^2= +ou - √7
x'= √7 ou x"= -√7
x= +/-√4
x'= √4=2 ou x"= -√4=2
Sagittarius:
ÓTIMA resposta
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás